(untitled) (Journal of the College of Basic Education, 2022)
In this paper, we will study the concepts of continuous cross-sectional fuzzy conic and prove the Schauder fixed point theorem in "intuitive fuzzy conic metric spaces as a generalization of the fuzzy metric conic space and prove another version of the Schauder fixed point theorem in the intuitive fuzzy metric conic space as a generalization" of other types of point theorems fixed in the intuitively blurry conic metric space that other researchers are studying, as well as to the usual intuitively blurry conic metric space.